Evidence of widespread declines in Kenya's raptor populations over a 40-year period. (February 2022) - Ogada, Darcy; Virani, Munir Z.; Thiollay, Jean Marc; Kendall, Corinne J.; Thomsett, Simon; Odino, Martin; Kapila, Shiv; Patel, Teeku; Wairasho, Peter; Dunn, Leah; Shaw, Phil
Abstract: Kenya's wildlife has been declining substantially for decades, due to rapid human population growth and its associated impacts on natural habitats. Predators and scavengers are particularly sensitive to anthropogenic pressures, and their changing status has corresponding impacts on the ecosystem services they provide. To estimate rates of change in Kenya's raptor populations we compared linear encounter rates (individuals 100 km −1 ) recorded during road surveys conducted in 1970–1977 and 2003–2020. Encounter rates for 19 out of 22 species examined had fallen, by a median of 70% among those showing a significant or near-significant change. No species had increased significantly. Declines had occurred among all vulture and large eagle species, and were especially pronounced among once-common small and medium-sized raptors. Our findings demonstrate the importance of protected areas (PAs) for Kenya's remaining raptor populations. The median encounter rate for vultures and large eagles had dropped by 23% within PAs and by 76% in unprotected areas. Smaller species showed divergent trends in relation to PA status, their median encounter rate increasing by 104% within PAs while declining by 85% elsewhere. Based on projected declines over three generation lengths, 45% of the species examined would qualify as nationally Endangered or Critically Endangered. Key threats include electrocution/collision with energy infrastructure, deliberate and incidental poisoning, and impacts associated with habitat degradation. Kenya's raptor declines could be reversed through enhanced management of PAs, mitigation of specific threats and the implementation of species recovery plans; all requiring steadfast government commitment and close collaboration with conservation stakeholders.